CHILDREN’S PEDESTRIAN TRAUMAS (PROBLEMS AND THE WAYS OF DECISION) - R.A. Keshishyan (Вопросы современной педиатрии, 2009)
The article presents the analysis of pedestrian traumas in the world and in Russian Federation. The basic principles of reorganization strategy of traffic security for the achievement of fundamental changes in the questions of decreasing of accidents’ rate with participation of children and lessening the severity of medical consequences of trauma, basing on the principles of in- and interdepartmental integration.Key words: children, pedestrian traumatism, epidemiology.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(4):18-22)